Ethnobotanical and Pharmacological Evaluation of Indian Medicinal Plants: Towards Evidence-Based Applications - Vinodkumar Sarup Didwana,; Dr. Navneet Sharma, (The Bioscan, 2025)
India's vast ethnobotanical heritage offers a reservoir of traditional medicinal knowledge, much of which remains underexplored in modern pharmacological contexts. This study evaluates the ethnobotanical usage and pharmacological validation of Indian medicinal plants to highlight their therapeutic potential and identify avenues for evidence-based applications. Through a comprehensive review of over 120 ethnobotanical and scientific studies, we identified key plant species traditionally used to treat ailments such as inflammation, infections, metabolic disorders, and cardiovascular conditions. About 60% of the most cited plants have been pharmacologically investigated, with many demonstrating significant bioactivity in preclinical trials. However, discrepancies between traditional claims and scientific outcomes point to the need for standardized methodologies and clinical validation. This research underscores the importance of integrating traditional knowledge with modern pharmacological approaches to develop safe, effective, and sustainable herbal therapies. Ethical bioprospecting, community involvement, and policy reform are vital to bridge the gap between tradition and modern medicine.